2015
DOI: 10.1109/tbme.2014.2378553
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the Biomechanical Effects of Compression Therapy by Finite Element Modeling and Ultrasound Elastography

Abstract: The discussion of this paper highlights the benefits of using elastography to reconstruct patient-specific FE models of soft tissues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 37 publications
1
33
0
Order By: Relevance
“…In a previous study [1], the material properties of superficial soft tissues were measured using ultrasound elastography (USE). In another previous study [2], the material properties of the deep soft tissues were identified by an inverse method.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…In a previous study [1], the material properties of superficial soft tissues were measured using ultrasound elastography (USE). In another previous study [2], the material properties of the deep soft tissues were identified by an inverse method.…”
Section: Methodsmentioning
confidence: 99%
“…The same four volunteers (3 males and 1 female, mean age 27 years) than those of previous studies [1,2] are considered. On each of them, MRI scan and USE data were acquired, whereas a local compression test was also carried out on the right hand side calf.…”
Section: Data Acquisitionmentioning
confidence: 99%
See 3 more Smart Citations